2017
DOI: 10.5978/islsm.17-or-2
|View full text |Cite
|
Sign up to set email alerts
|

Low Level Laser Therapy in patients with chronic foot and ankle joint pain

Abstract: Background and Aims: Chronic foot and ankle joint pain is one of the most frequent complaints which is regularly seen in the out-patient clinic of our medical institute. In previous studies we have reported on the benefits of low level laser therapy (LLLT) for chronic pain in the elbow, hand, finger and the lower back. The present study examined the effects of LLLT on chronic foot and ankle joint pain. Materials and Methods: Over the past 5 years, 17 subjects visited the out-patient clinic with complaints of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Additionally, relieving pain caused by the in ammatory response is another essential problem in treating soft tissue injuries. Izukura et al [19] selected 17 patients with chronic foot and ankle pain as complaints. The patients underwent Ga-Al-As semiconductor laser irradiation at a wavelength of 830 nm, power density of 667 mW/cm 2 , and energy density of 20 J/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, relieving pain caused by the in ammatory response is another essential problem in treating soft tissue injuries. Izukura et al [19] selected 17 patients with chronic foot and ankle pain as complaints. The patients underwent Ga-Al-As semiconductor laser irradiation at a wavelength of 830 nm, power density of 667 mW/cm 2 , and energy density of 20 J/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] In previous ankle sprain studies, LLLT has shown a signi cant e cacy and a certain dose-response related-relationship. [18][19][20] However, the doseresponse relationship of LLLT in chronic ankle sprain treatment has not been published, and the therapeutic effect, intensity, and dosage required for chronic ankle sprain patients still need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…74 North American Association for Laser Therapy conference has also recommended not using LLLT directly over the developing fetus during pregnancy. [82][83]…”
Section: Physical Medicine and Rehabilitationmentioning
confidence: 99%